2009
DOI: 10.1039/b914187a
|View full text |Cite
|
Sign up to set email alerts
|

A cryogenic direct-plotting system for fabrication of 3D collagen scaffolds for tissue engineering

Abstract: The goal of tissue engineering is to repair or regenerate damaged tissue using a combination of cellular biology and materials engineering techniques. One of the challenging problems in tissue engineering is the development of a reproducible three-dimensional (3D) scaffold to support cell migration and infiltration. Although natural polymers, such as dissolved collagen or alginate, are considered ideal for this purpose, their hydrophilic properties have hindered the fabrication of designed 3D scaffold structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 43 publications
0
80
0
Order By: Relevance
“…However, the fabricated collagen scaffold has a broad pore-size distribution; moreover, the controllability of pore structure within the scaffold was impossible. To overcome these fabrication challenges, an indirect solid free form fabrication and low temperature direct plotting method was used [44,45]. In recent, we fabricated pore-size controlled collagen scaffolds and we used it in skin tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fabricated collagen scaffold has a broad pore-size distribution; moreover, the controllability of pore structure within the scaffold was impossible. To overcome these fabrication challenges, an indirect solid free form fabrication and low temperature direct plotting method was used [44,45]. In recent, we fabricated pore-size controlled collagen scaffolds and we used it in skin tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, scaffolds extruded at room temperature generally have a higher density, compared to scaffolds established by extrusion combined with freeze drying [28, 29]. It was found that filter pressing, thread thickness, and thread stability during extrusion and after drying are influenced by the combination of steric and electrostatic additives in the composition.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques can also produce desired pore sizes and mechanical properties for specific applications [18]. Researchers have recently turned to three-dimensional plotting techniques for scaffolds that require precise control of scaffold design [19,20]. To apply the three-dimensional plotting technique to natural polymers, the processes cannot require heating, high pressure, harsh solvents, or post-processing; consequently, bio-components such as proteins or cells can also be included in the fabrication process [21].…”
Section: Introductionmentioning
confidence: 99%